Al Ain Oases Mapping Project: Qaṭṭārah Oasis, past and present (poster) - Power, Timothy; Sheehan, Peter (Proceedings of the Seminar for Arabian Studies, 2016)
The Al Ain Oases Mapping Project is a collaboration between the Abu Dhabi Tourism and Culture Authority and Zayed University. It aims to document the present oasis landscape and identify surviving historic components, while at the same time engaging Emirati students with their heritage and building capacity for archaeology in the UAE. The project utilizes a non-intrusive field-walking methodology suitable for a class of undergraduate students. It further draws on the students’ community links and bilingualism to contact former residents of the oasis villages and undertake oral history interviews. The first season’s work focused on Qaṭṭārah Oasis and contributes to the established programme of works there; future seasons will expand the survey to neighbouring Jīmī Oasis and the other oases of al-ʿAyn. The results will inform continued archaeological exploration of the oases by TCA.